2016
DOI: 10.2522/ptj.20150079
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Implementation in a Skilled Nursing Facility: Case Report for Physical Therapist Practice in Washington

Abstract: Human factors, such as the need for provider education in appropriate bedside manner with a telehealth session, were identified. Since 2011, more than 1,000 telehealth physical therapy sessions were conducted at Infinity Rehab SNFs in Washington State. In the future, alternative payment models focused on valued-based clinical outcomes may facilitate wider telehealth adoption in physical therapy. Future research on efficacy and cost-effectiveness is needed to promote broader adoption of telehealth physical ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
1
14
0
2
Order By: Relevance
“…While acknowledging that a national policy for investment in eHealth interventions is crucial to its adoption, Rozenblum et al [ 132 ] argued that financial incentives should be based on patient outcomes that might ensue from the eHealth intervention. DeWorsop et al [ 129 ] and Lee and Billings [ 133 ] reported on the importance of cost effectiveness to promoting the adoption of eHealth interventions.…”
Section: Resultsmentioning
confidence: 99%
“…While acknowledging that a national policy for investment in eHealth interventions is crucial to its adoption, Rozenblum et al [ 132 ] argued that financial incentives should be based on patient outcomes that might ensue from the eHealth intervention. DeWorsop et al [ 129 ] and Lee and Billings [ 133 ] reported on the importance of cost effectiveness to promoting the adoption of eHealth interventions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in an in-depth literature review of 225 articles focused on videoconferencing in clinics, one finding was the importance of developing protocols for using the system, which is a component of packaging the programme 19 and other studies have supported these findings. 20 Perceived usefulness of and interest in telemedicine has previously shown to increase probability of PCPs using telemedicine options. 21 Previous research has also shown the importance of reflecting and evaluating related to telehealth nursing services 22 and the challenges associated with integrating new and 'different' models of practice into deeply embedded local working structures (compatibility).…”
Section: Leadership Supportmentioning
confidence: 99%
“…We implemented the current quality improvement project to provide VA specialty medical care and mental health support via telehealth to a subgroup of Eastern Colorado Health Care System (ECHCS) Veterans who reside in contracted Community Nursing Homes (CNHs). The few studies published providing elderly or nursing home care via telehealth suggest positive health outcomes, cost benefits, and staff satisfaction for patient glycemic management [8]; rehabilitation after a stroke, fall, fracture, or prolonged hospital admission [9]; continence assessment and management [10]; after hours primary care [11]; and physical therapy [12]. Evidence is also beginning to demonstrate that tele-psychiatry is a viable substitute for face-to-face visits to treat depression in elderly patients [13].…”
Section: Introductionmentioning
confidence: 99%